Evaluation of oral health status of 15 years old school going children in district Indore, Madhya Pradesh, India - Singh, Varsha; Sethi, Anuj Shamsher (International Journal of Advances in Medicine, 2019)
Background: Dental caries and Gum diseases are the major public health problem in developed and developing countries both and the prevalence is more during the childhood specially in lower socioeconomic strata of our society so present study was conducted to find out the prevalence of dental and gum diseases among the 15 years of age school going children. Methods: This study was conducted among 15 years old children of government rural schools in the catchment area of Sri Aurobindo Institute of Medical Sciences, District Indore after getting ethical approval from institutional ethical committee, 400 students were included till the required sample size was achieved. Oral cavity examination was done by a team of evaluated for oral health status by a trained examiner who took training in department of community dentistry and Pedo-odontology. Data was entered and analysed by using SPSS. Results: Present study reveals that 38% of participants had dental decay out of which was more there in boys and found statistically significant <0.05. Majority of participants (70%) had normal gums only 4% had bleeding gums. 9% of the the participants had hypoplastic enemal. Conclusions: The current study explores that the dental decay is the major oral health problem followed by calculus. Oral health education and oral cavity examination should be done at a regular interval study.